Spontaneous formation of wrinkle-driven tubular structure as a versatile platform for adaptive 3D stretchable electronics. Issue 9 (18th June 2020) - Zeng, Songshan; Li, Rui; Tait, William R. T.; Smith, Andrew T.; Zhang, Monica; Zhu, Mengting; Chov, Nora; Xu, Gefan; Zhang, Dianyun; Sun, Luyi
Abstract : A 3D tubular structure fabricated from the relaxation of pre-stretched 2D precursor is used to develop various 3D stretchable electronics. Abstract : A stretchable, 3D tubular structure formed due to processing-induced wrinkles is proposed as a platform to develop adaptive stretchable electronics. This integrated structure is fabricated by releasing a pre-stretched 2D film-substrate precursor, resulting in a wrinkled surface, that shows a strong directional dependence that drives the tube formation. This 3D shape adaptivity can control the radial opening and closing of the tube through longitudinal strain, which inspires the development of a dual-channel piezoresistive strain sensor/switch concomitant with mechanochromic effect and an intriguing tactile responsive artificial Mimosa pudica device. In addition, the system is compatible with 2D film deposition technologies, which allows customized electrode patterns to be coated on the pre-stretched 2D precursor followed by wrapped inside as precursor released. Upon sealing the tube, this "coating and self-wrapping" feature allows for the invention of a highly stretchable tactile switch, and a stretchable tubular supercapacitor with dual stimuli-responsiveness.